Inducible NOS mediates CNP-induced relaxation of intestinal myofibroblasts - Yishi Chen (2018)
Contraction of intestinal myofibroblasts (IMF) contributes to the development of strictures and fistulas seen in inflammatory bowel disease, but the mechanisms that regulate tension within these cells are poorly understood. In this study we investigated the role of nitric oxide (NO) signaling in C-type natriuretic peptide (CNP)-induced relaxation of IMF. We found that treatment with ODQ, a soluble guanylyl cyclase (sGC) inhibitor, or NG-nitro-L-arginine (L-NNA) or NG-monomethyl-L-arginine (L-NMMA), inhibitors of NO production, all impaired the relaxation of human and mouse IMF in response to CNP. ODQ, L-NNA, and L-NMMA also prevented CNP-induced elevations in cGMP concentrations, and L-NNA or L-NMMA blocked CNP-induced decreases in myosin light phosphorylation. IMF isolated from transgenic mice deficient in inducible nitric oxide synthase (iNOS) had reduced relaxation responses to CNP compared with IMF from control mice and were insensitive to the effects of ODQ, L-NNA, and L-NMMA on CNP treatment. Together these data indicate that stimulation of sGC though NO produced by iNOS activation is required for maximal CNP-induced relaxation in IMF. © 2013 the American Physiological Society.